Tailorable coaxial carbon nanocables with high storage capabilities. Issue 42 (20th October 2017) - Guan, Guozhen; Deng, Jue; Ren, Jing; Pan, Zhiyong; Zhuang, Wen; He, Sisi; Wang, Bingjie; Che, Renchao; Peng, Huisheng
Abstract : A new family of coaxial carbon nanocables is designed with the ability to be tailored into desired diameters, lengths and components through a low-cost, high-efficiency slicing process. These nanocables are promising for the storage of materials and ions, and their incorporation into lithium-ion batteries demonstrates their high specific capacities. Abstract : The preparation of nanomaterials into required sizes, structures and components is critical but remains challenging for practical applications. Here, coaxial nanocables were designed with the ability to be tailored into desired diameters, lengths and components through a low-cost, high-efficiency slicing process. The nanocables were radially grown from carbon nanotube cores with coaxial graphene or heteroatom-doped graphene sheet sheaths. This approach allowed the thickness to be fine-tuned, and the increased modulus from the sheath made the nanocables tailorable. The nanocables exhibited an aligned structure and were able to be cut into thin films with accurately controlled thicknesses ranging from tens of nanometers to micrometers while the two ends were left open. These nanocables are promising for the storage of materials and ions, and their incorporation into lithium-ion batteries demonstrates their high specific capacities.